Radiating Petals: A Case of Planum Sphenoidale Meningioma Presenting with Seizures and Anosmia, Resected via Suprabrow Keyhole Craniotomy - Goutham M; Dr Mayur Vinay Kaku (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Planum sphenoidale meningiomas are uncommon anterior skull-base tumors that classically present with anosmia, seizures, and behavioral change once they reach sufficient size to compress adjacent neurovascular structures. Case Presentation: We report a 44-year-old woman who presented with seizures, progressive anosmia, and behavioral change that progressed to altered sensorium refractory to anticonvulsant therapy (Glasgow Coma Scale 6/15). Contrast-enhanced magnetic resonance imaging (MRI) demonstrated a large extra-axial anterior cranial fossa mass (6.2 × 5.9 × 4.5 cm) involving the cribriform plate, nasal cavities, olfactory groove, orbital roof, sella, and clinoidal triangle. The patient underwent a suprabrow keyhole craniotomy through a 4 × 1 cm bone window, with complete microsurgical excision of the tumor. Histopathology confirmed a WHO Grade 1 meningioma, and the patient had an uneventful recovery with a favorable cosmetic outcome. Conclusion: Multi-structural extension of planum sphenoidale meningiomas can produce a combination of seizures, anosmia, and behavioral disturbance. The suprabrow keyhole craniotomy is a safe, effective, and cosmetically favorable alternative to conventional transcranial approaches for complete excision of these tumors.